The Concept of Eco-administrative Unit (Ecosystem Approach in Forest and Wildlife Conservation) - Rishi, Vinod (Indian Forester, 2005)
The ecological boundaries of natural forest ecosystems often do not coincide with the administrative boundaries of the forest or protected area management units. In order to accommodate the principle of sustainable use of forest based renewable natural resources by human populations living in and around the natural ecosystems for ensuring forest and wildlife conservation the paper describes the concept of Eco-administrative unit as basic unit for planning ecosystem based management of areas situated in and around the forests and wildlife habitats.